The Effect of Service Quality and Price Factors on Customer Satisfaction of Tsamie Noodle Bar in Indonesia: an Islamic Perspective - Ane Khoerunisya; Farid Al Rizky; Siti Nurhasanah; Tomy Saladin Aziz; Abdul Aziz (El-Qish: Journal of Islamic Economics, 2023)
This research has high significance in the context of business and customer service. By analyzing the effect of service quality and price on customer satisfaction at Tsamie Noodle Bar, this study provides business owners and restaurant managers with valuable insights into the factors that influence customer satisfaction. With a better understanding of how service quality and price can affect customer perceptions and satisfaction, business owners can take appropriate steps to improve the customer experience and strengthen their customer base. In addition, this research also has relevance to the principles of Islamic economics, where providing satisfaction to consumers is an integral part of a trader's responsibility. This research problem focuses on the effect of service quality and price on customer satisfaction at Tsamie Noodle Bar. For this reason, this study uses a survey method with a quantitative approach to 100 respondents using probability sampling techniques. Data collection techniques through questionnaires and documentation with multiple linear regression analysis using SPSS software version 22. The research findings show that service quality and price have a positive and significant influence on customer satisfaction at Tsamie Noodle Bar. This means that the better the quality of service provided to consumers and the fairer the price offered, the more satisfied consumers will be.